Effect of different levels of fermented rice bran for the growth of jelawat, Leptobarbus hoevenii - HENDRY YANTO; JUNIANTO JUNIANTO; RITA ROSTIKA; YULI ANDRIANI; UJANG HIDAYAT TANUWIRIA (Smujo International, 2018)
Yanto H , Junianto , Rostika R, Andriani Y, Tanuwiria UH. 2018. Effect of different levels of fermented rice bran for the growth of jelawat, Leptobarbus hoevenii. Nusantara Bioscience 10: 81-86. The prime objective of this study is to find the optimum level of fermented rice bran in diets beneficial to improve the digestive enzyme activity, growth and feed efficiency for jelawat (Leptobarbus hoevenii Bleeker). Different levels of fermented rice bran in the diets, i.e., A1 (10%), A2 (20%), A3 (30%), A4 (40%), and A5 (10% non-fermented rice bran), as well as A6 (10% commercial diet) was designed as a treatments during the study. The experimental diets with the same protein (isonitrogenous) and energy (isocaloric) were fed to jelawat fingerlings with an average of 32.57±0.15 g per fish. The results showed that amylase activities were significantly increased with the increased level of fermented rice bran levels in the diets and it was significantly different among the treatments (P<0,05). Proteins and lipids contents of the body and their retention rate, daily growth rates, and feed efficiencies were also significantly different among the treatments (P<0.05). It was concluded from the present investigation that up to 30% of fermented rice bran in the diet was best for jelawat with an optimum level of 25.66-26.78% for the growth performance and feed efficiency of jelawat.